STRATEGIC RECONFIGURATION AND MANAGEMENT OF RETAIL CENTRES CREATING COMPETITIVE ADVANTAGE THROUGH COMMUNICATIVE COMPETENCE - Tore Omholt (Asian Academy of Management Journal, 2002)
In the last decade, the retail industry in many countries, including some Asian countries has undergone great changes due to a more dynamic and turbulent environment. This amongst other things has led to a concentration of retail functions in out-of-town regional shopping centres. This development can be explained by pointing to the traditional, segmentalist ways of strategic management in the retail sector, which to a large degree has looked upon location as the most important, and in many cases, the only source of competitive advantage. It has also treated the retail centre as a nexus of contracts based in turn on a series of bilateral contracts. These ways are in our opinion no longer able to deal with an increasingly dynamic environment, especially in traditional town centres. We are given some examples, however, where successful strategic response is characterized by extensive market research and intimate consumer knowledge, but these kinds of capabilities or skills seem to be confined to the typical multinational chain organization. One seldom finds innovative town centres or dynamic shopping centres with similar capabilities. Our view is that a dynamic reconfiguration will have to take place and be coordinated in a more multilateral fashion without having to resort to excessive communication and information processing to achieve a transformative reconfiguration. In this paper we have tried to show that an approach based on a socio-cybernetic framework and the development of several types of communicative competences, may be effective for the development of competitive advantage for a retail centre.